2020
DOI: 10.1111/tra.12731
|View full text |Cite
|
Sign up to set email alerts
|

ESCRT‐dependent protein sorting is required for the viability of yeast clathrin‐mediated endocytosis mutants

Abstract: Endocytosis regulates many processes, including signaling pathways, nutrient uptake, and protein turnover. During clathrin-mediated endocytosis (CME), adaptors bind to cytoplasmic regions of transmembrane cargo proteins, and many endocytic adaptors are also directly involved in the recruitment of clathrin. This clathrin-associated sorting protein family includes the yeast epsins, Ent1/2, and AP180/PICALM homologs, Yap1801/2. Mutant strains lacking these four adaptors, but expressing an epsin N-terminal homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…In foundational studies, it was determined that secretory mutants display defects in endocytosis in the model S. cerevisiae (50). Recently, a clear linkage between clathrinmediated endocytosis and the endosomal sorting complex required for transport (ESCRT)-dependent protein sorting pathway has been identified in S. cerevisiae (51). There it was found that members of the ESCRT complex are required for the viability of cells lacking the epsins Ent1p and Ent2p in which one ENTH domain has been reintroduced (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In foundational studies, it was determined that secretory mutants display defects in endocytosis in the model S. cerevisiae (50). Recently, a clear linkage between clathrinmediated endocytosis and the endosomal sorting complex required for transport (ESCRT)-dependent protein sorting pathway has been identified in S. cerevisiae (51). There it was found that members of the ESCRT complex are required for the viability of cells lacking the epsins Ent1p and Ent2p in which one ENTH domain has been reintroduced (51).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a clear linkage between clathrinmediated endocytosis and the endosomal sorting complex required for transport (ESCRT)-dependent protein sorting pathway has been identified in S. cerevisiae (51). There it was found that members of the ESCRT complex are required for the viability of cells lacking the epsins Ent1p and Ent2p in which one ENTH domain has been reintroduced (51). In the prevacuolar secretory pathway, S. cerevisiae VPS1 contributes to endocytosis as well (52).…”
Section: Discussionmentioning
confidence: 99%
“…As non-senescent cellular environment of BMSCs internalized exosomes exclusively via clathrin-mediated endocytosis, senescent BMSCs required additional involvement of macropinocytosis and caveolae-mediated endocytosis to mediate the internalization of exosomes. Clathrin-mediated endocytosis was reported as the common endocytic channel that play an important role in the positive regulation of many intracellular signaling cascades ( Hoban et al, 2020 ; Johnson et al, 2021 ). Caveolae was the most commonly reported non-clathrin coated plasma membrane buds with flask-shaped invaginations that existed on the surface of many mammalian cell types including smooth muscle, type I pneumocytes, fibroblasts, adipocytes, and endothelial cells ( Nanbo et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, poly (ADP-ribose) polymerase inhibitors (PARPi) operate through a “synthetic lethality” mechanism with mutant DNA repair pathways genes in cancer cells, and PARPis are widely used in cancer such as ovarian cancer ( 57 ). There are two forms of VPS4 in the human body and recently it is confirmed that VPS4A and VPS4B are essential enzymes for the ESCRT pathway and have no substitution ( 58 ), loss of both is fatal ( 59 ).…”
Section: Possible Mechanisms Affecting Carcinoma Of Vps4mentioning
confidence: 99%